IoT based medicine dispenser for improving medication adherence - Raisa, Fatima Fairuz; Orthy, Nishat Tasneem; Nibir, MD Imran Sarder; Faysal, Hossain Muhammad (Brac University, 2023)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.